Perubahan Biologis Awal Berahi Kambing Kaligesing Betina yang Disuntik Ekstrak Hipofisa dengan Level Berbeda - Teguh Priatin; Faruq Iskandar; Hanung Dhidhik Arifin (Universitas Muhammadiyah Purworejo, 2019)
The purpose of this study was to determine the effect of different levels of pituitary extract administration on changes in vulva and cervical mucus secretion as indicators of lust for Kaligesing female goats. The research process was carried out at the Integrated Laboratory of Muhammadiyah University Purworejo and in Donorejo Village, Kaligesing District, Purworejo Regency, Central Java Province. The material used in this study was 24 Kaligesing female goats aged 2-5 years who had given birth at least once. The ingredients used are the pituitary gland and Medroxy progestagen acetate. The treatments given were T0 (injected 5 ml physiological NaCl 0.9%), T1 (injected pituitary extract 0.25 g in 5 ml physiological NaCl 0.9%) and T2 (injected pituitary extract 0.50 g in 5 ml NaCl physiological 0.9%). The experimental design used in this study was a complete randomized design subsampling (CRD) with 3 treatments and 8 replications. The parameters observed were vulva discoloration, swelling of the vulva, increase in temperature of the vulva, abundance of cervical mucus, and nerve mucus fern. The data obtained were analyzed using Chi-square and ANOVA. The results showed that the administration of pituitary extract had no effect (P> 0.05) on all parameters. Vulva color score at T0: 1, 5, 2; T1: 1, 4, 3 and T2: 0, 5, 3. The swelling of the vulva at T0, T1, and T2 is 0.350 cm, 0.375 cm, 0.387 cm. The increase in temperature at T0, T1 and T2 is 0.375 oC, 0.40 0oC, 0.56 2oC. Cervical lender abundance score at T0: 5, 2, 1; T1: 3, 3, 2, and T2: 2, 4, 2. The fern score of the cervical lender at T0: 1, 1, 4, 1, 1, 0; T1: 1, 1, 1, 5, 0, 0 and T2: 0, 0, 1, 2, 2, 3. The pituitary extract can improve the appearance of heat among treatments but is not significant (P> 0.05). Based on the results of the study, it can be concluded that: Giving pituitary extract in women Kaligesing Goat can improve the appearance of heat that is seen from changes in the color of the vulva, swelling of the vulva, increase in temperature of the vulva, the number of cervical mucus and cervical mucus fern, but not yet significant.